Geograf globus propil als Beitrag zur Förderung der Lerner*innenautonomie in der Schule - Magdalena Kaltseis; Eva Binder (DiSlaw, 2024)
Since the 1970s, learner autonomy has been a widespread and popular concept in education. This term generally involves helping learners become more independent in their learning process and taking responsibility for their own learning. Notwithstanding this positive attempt to improve learners’ independence and strengthen their personal responsibility, promoting learner autonomy is far from being self-evident in today’s foreign language classroom. The current article, therefore, takes a closer look at learner autonomy and summarizes the main suggestions for fostering learner autonomy provided in the research literature. Subsequently, the film The Geographer drank his globe away is discussed as a cinematic approach to learner autonomy. In the final section, ideas are presented on how to develop learner autonomy in the foreign language classroom with the help of the film.